2011
DOI: 10.1002/prot.22975
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the GABAA receptor structure and orthosteric ligand binding: Receptor modeling guided by experimental data

Abstract: GABA A receptors (GABA A Rs) are ligand gated chloride ion channels that mediate overall inhibitory signaling in the CNS. A detailed understanding of their structure is important to gain insights in e.g. ligand binding and functional properties of this pharmaceutically important target. Homology modeling is a necessary tool in this regard because experimentally determined structures are lacking. Here we present an exhaustive approach for creating a high quality model of the α 1 β 2 γ 2 subtype of the GABA A R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
42
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 79 publications
11
42
0
2
Order By: Relevance
“…Taken together with the present data, it is attractive to speculate that the tricyclic oxazolo-2,3-benzodiazepine (OBDZ) scaffold of the compounds reported here has the same role as the PIOL scaffold i.e. anchor the compound in the GABA binding-pocket (Sander et al, 2011). The stringent requirement of the regiochemistry of the oxazolone ring is in line with this notion.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Taken together with the present data, it is attractive to speculate that the tricyclic oxazolo-2,3-benzodiazepine (OBDZ) scaffold of the compounds reported here has the same role as the PIOL scaffold i.e. anchor the compound in the GABA binding-pocket (Sander et al, 2011). The stringent requirement of the regiochemistry of the oxazolone ring is in line with this notion.…”
Section: Discussionsupporting
confidence: 76%
“…Previously, Frølund and co-workers have reported a series of GABA A orthosteric antagonists based on the 5-(4-piperidyl)-3-isoxazolol (PIOL) scaffold (Frølund et al, 2005;Frølund et al, 2007;Frølund et al, 2002). These studies indicated that the PIOL moiety interacts with amino acid residues also known to be required for the binding to GABA at the  subunit interface (Sander et al, 2011). Phenyl-PIOL compounds behaved as competitive antagonists of GABA, moreover, bulky hydrocarbon ring substitutions of PIOL were also tolerated and in some cases increased the affinity of the compounds (Frølund et al, 2005;Frølund et al, 2007;Frølund et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…These studies also indicate that such a strong inter-interface interaction can be greatly aided through halogen bonding. The compound-mediated contacts between the two subunits in the binding interface has also been suggested to be important for the efficacy on GABA A receptors (69), and it is, therefore, likely to be a general feature for the Cys-loop receptors.…”
Section: Evaluation Of Ls-achbp As Model System For Nachr ␣4␤2mentioning
confidence: 99%
“…This “ligand-centric” approach has been widely employed in identification of novel inhibitors against GPCR targets including MCH-R1, mGluR and CCR2 [29, 34, 3739]. Other applications include protein structural analysis and function prediction [4045], understanding of protein-ligand interactions [4653] and compound optimization [5456]. Successful stories for drug design starting from homology models are listed in Table 4.…”
Section: Protein Modelingmentioning
confidence: 99%
“…Some applications include protein structural analysis and function prediction [4045], understanding of protein-ligand interactions [4653] and compound optimization [5456]. In order to compensate from the low-resolution models, additional target-specific constraints and/or more accurate scoring function are often applied.…”
Section: Targeting Protein-ligand Interactionmentioning
confidence: 99%